Revisão anatômica para definição do ligamento hioepiglotico - Freitas, Emília Cristina Benevides de (1993)
Fifty six larynx from adults human corpses were macroscopically studied. Twenty-nine were fixed and twenty-seven were not. From the fixed ones, sixteen were useful for the microscopic study. ln the group with fixed larynx, twelve had mole characteristics and seventeen female. The non-fixed group had seventeen males and ten females. There was a strong laminate and transverse ligament, fanshaped, with the largest fixation at the hyoid bone. That ligament was formed by collagen and elastic fibers, more with collagen ones. Collagen fibers were more condensate close to the hyoid bone, while elastic fibers were more condensate near the epiglottis cartilage. lt seems to be correct that the hyoepiglottis ligament can interfere in the larynx's dynamics moving up and down the epiglottis as well as helping the rising of the larynx.